THE EFFECT OF TOURIST ATTRACTIONS AND AMENITIES ON VISITOR SATISFACTION AT THE COBAN LANANG WATERFALL TOURIST DESTINATION BATU CITY: THE EFFECT OF TOURIST ATTRACTIONS AND AMENITIES ON VISITOR SATISFACTION AT THE COBAN LANANG WATERFALL TOURIST DESTINATION BATU CITY - Chothofiah, Afrinarizqi; Anam, Mochammad Musafa'ul; Sandhubaya, Gilang (Jurnal Pariwisata Tourista, 2025)
Coban Lanang Tourism Destination is a natural educational tour in the form of a waterfall that prioritizes education, nature conservation, and a sustainable environment. Visitor satisfaction is a factor that plays a major role in a tourist destination. The purpose of this study was to determine the effect of tourist attractions and amenities on visitor satisfaction at the Coban Lanang Waterfall tourism destination. The study used 92 tourists who had visited the Coban Lanang Waterfall as respondents. This research method uses a descriptive quantitative method. The data collection technique was guided by a questionnaire which was measured using a Likert scale. The results of the research are (1) Tourist Attraction affects Visitor Satisfaction at Coban Lanang Waterfall Tourism Destinations, (2) Amenity affects Visitor Satisfaction at Coban Lanang Waterfall Tourism Destinations, (3) Tourist Attractions and Amenities together have influence on Visitor Satisfaction at Coban Lanang Waterfall Tourism Destinations.